The therapeutic challenge of giant splenic artery aneurysm: a case repport - Kauffman,Paulo (2017)
ABSTRACT Giant splenic artery aneurysm is a rare condition that represents an eminent life threatening for the patient, requiring, therefore, urgent surgical correction. A 61-year-old woman, former smoker, hypertensive, hypercholesterolemic and multipara sought our service because of a large tumor in the mesogastrium, which was an abdominal ultrasound finding. Despite the size of the tumor, the patient was asymptomatic. The angiotomography and the magnetic resonance image of the abdomen were suggestive of giant splenic artery aneurysm with more than 10cm in diameter that was confirmed by an angiography. She underwent surgery, open splenectomy, and partial aneurysmectomy. The approach of the celiac artery, which was ligated, was only possible with medialvisceral rotation because there was no possibility to view it through the anterior access. The histopathological test of aneurysmatic wall revealed atheroma plaques in the intima. The patient progressed without complications and she was discharged cured. In general, giant splenic artery aneurysms are symptomatic, however, as in the case we report, it may be asymptomatic and found in abdominal imaging exam. Although less invasive Interventional methods exist, such as laparoscopy and endovascular techniques, they were considered inappropriate in this case. Conventional open surgery should be the therapy of choice for a giant splenic artery aneurysm.